Cr (VI)-induced oxidative damage impairs ammonia assimilation into organic forms in Solanum lycopersicum L. - Maria Martins (Elsevier, 2021)
Chromium (Cr) is a dangerous metal that has been found in the environment in high amounts as the result of numerous human activities, with proven negative effects on various organisms, including plants. The exposure of some plant species to this metal resulted in reduced growth, impaired nutrient uptake, and led to an overproduction of reactive oxygen species (ROS), ultimately causing oxidative damage. Nevertheless, studies regarding the impact of Cr on nitrogen (N) metabolism, the main limiting factor for plant growth, either directly or through the occurrence of oxidative stress, are scarce. Thus, this work aimed to explore the interplay between ammonia (NH4+) assimilation, redox homeostasis and antioxidant (AOX) system of tomato plants exposed to increased concentrations of Cr (VI) (0, 5 and 10 µM). The results revealed that Cr (VI) induced biometric damages, with roots being the most affected organ. Glutamine synthetase (GS) was differentially influenced by the metal at the gene expression, protein and activity levels, whereas glutamate dehydrogenase (GDH) activity was enhanced. Moreover, in Cr (VI)-treated plants, the observed oxidative damage was dependent on metal concentration and plant organ, with a differential accumulation of ROS and a generalized increase of lipid peroxidation (LP) recorded, being paired with an overall failure of the enzymatic antioxidant (AOX) system. Still, the non-enzymatic AOX component had a relevant role in the protection of plants against Cr (VI). Overall, the obtained results suggest that Cr (VI)-mediated plant growth reduction resulted from the occurrence of oxidative stress, coupled with the lack of enzymatic AOX defense, which, consequently, affected the NH4+ assimilatory route.